An empirical study on the impact of Basel III standards on banks' default risk: The case of Luxembourg - Gastón Andrés Giordana; Ingmar Schumacher (Journal of Risk and Financial Management, 2017)
We study how the Basel III regulations, namely the Capital-to-Assets Ratio (CAR), the Net Stable Funding Ratio (NSFR) and the Liquidity Coverage Ratio (LCR), are likely to impact banks' profitability (i.e., ROA), capital levels and default. We estimate historical series of the new Basel III regulations for a panel of Luxembourgish banks for a period covering 2003q2-2011q3. We econometrically investigate whether historical LCR and NSFR components, as well as CAR positions are able to explain the variation in a measure of a bank's default risk (approximated by Z-score) and how these effects make their way through banks' ROA and CAR. We find that the liquidity regulations induce a decrease in average probabilities of default. We find that the liquidity regulation focusing on maturity mismatches (i.e., NSFR) induces a decrease in average probabilities of default. Conversely, the impact on banks' profitability is less clear-cut; what seems to matter is banks' funding structure rather than the characteristics of the portfolio of assets. Additionally, we use a model of bank behavior to simulate the banks' optimal adjustments of their balance sheets as if they had to adhere to the regulations starting in 2003q2. Then, we predict, using our preferred econometric model and based on the simulated data, the banks' Z-score and ROA. The simulation exercise suggests that basically all banks would have seen a decrease in their default risk during a crisis episode if they had previously adhered to Basel III.
Keywords: G21; G28; 650; Basel III; bank default; Z-score; profitability; ROA; GMM estimator; simulation; Luxembourg